Promotion of mangrove-friendly shrimp aquaculture in Southeast Asia - Sulit, V.T.; Ebron, N.R.; Tendencia, I.T.; Gotera, S.C. (Tigbauan, Iloilo, Philippines SEAFDEC Aquaculture Department, 2004)
This publication comprises two major parts : Report on the Regional Seminar-Workshop on Mangrove-Friendly Shrimp Aquaculture, Bangkok, Thailand, 24-27 June 2003 ; Report on the Mangrove Friendly Shrimp Culture Project: Phase I (2000-2003)
Keywords: Shrimp culture; Mangrove; Asia